New optimized triazene radical initiators for thermal polymerization - Kang, Seokwoo; Jeong, Jinwook; Kim, Beomjin; Park, Young Il; Noh, Seung Man; Park, Jongwook (Journal of industrial and engineering chemistry (Seoul, Korea), 2019)
[Display omitted] New phenyl-triazine-containing thermal radical initiators (TRIs), namely 3,3-dimethyl-1-phenyltriazene (BTAM), 3,3-diethyl-1-phenyltriazene (BTAE), 2,2,6,6-tetramethyl-1-(phenyldiazenyl)piperidine (BTACM), 2,2,6,6-tetramethyl-1-(phenyldiazenyl)piperidin-4-ol (BTACH−OH), and 2,2,6,-tetramethyl-1-(phenyldiazenyl)piperidin-4-ol (BTACM−OH), were designed and synthesized for use in radical polymerization. The method used to synthesize the initiators was simple, and the synthesized initiators did not change the color of the polymer. For these five new initiators as well as four related previously designed ones, the polymerization conversion rate was in each case over 92%. BTACM, which also included a six-membered aliphatic ring substituted with two dimethyl groups, showed a polymerization time 81.9% less than that without initiator and showed according to DSC experiments the lowest peak polymerization temperature of 137°C. These results represent a new promising thermal initiator system expected to be effective for various applications, especially those involving polymer coating.